2005
DOI: 10.1084/jem.20042432
|View full text |Cite
|
Sign up to set email alerts
|

Defective NKT cell development in mice and humans lacking the adapter SAP, the X-linked lymphoproliferative syndrome gene product

Abstract: SAP is an adaptor protein expressed in T cells and natural killer cells. It plays a critical role in immunity, as it is mutated in humans with X-linked lymphoproliferative syndrome (XLP), a fatal immunodeficiency characterized by an abnormal response to Epstein-Barr virus (EBV) infection. SAP interacts with the SLAM family receptors and promotes transduction signal events by these receptors through its capacity to recruit and activate the Src kinase FynT. Because it has been previously established that FynT is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
248
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 305 publications
(260 citation statements)
references
References 24 publications
10
248
1
1
Order By: Relevance
“…This last observation suggested that the cd4-cre transgene was causing partial deletion of the sap gene in NK-T cells, in agreement with the fact that NK-T cells are derived from a CD4 ϩ CD8 ϩ T cell precursor (21). As reported (22)(23)(24), a severe reduction (Ϸ90%) of NK-T cell numbers was seen in conventional sap Ϫ/Ϫ mice (data not shown). In sap f l/f l ;lck-cre mice (Fig.…”
Section: Resultssupporting
confidence: 68%
“…This last observation suggested that the cd4-cre transgene was causing partial deletion of the sap gene in NK-T cells, in agreement with the fact that NK-T cells are derived from a CD4 ϩ CD8 ϩ T cell precursor (21). As reported (22)(23)(24), a severe reduction (Ϸ90%) of NK-T cell numbers was seen in conventional sap Ϫ/Ϫ mice (data not shown). In sap f l/f l ;lck-cre mice (Fig.…”
Section: Resultssupporting
confidence: 68%
“…This hypothesis suggests that Va14i + thymocytes undergo 'agonist selection', which leads to the activated/ memory phenotype on mature iNKT cells without (known) exogenous antigen encounter [46]. Another feature of iNKT cell development that is far afield from conventional T cell development is the requirement for signaling lymphocyte activation molecule (SLAM)-associated protein signaling through the tyrosine kinase Fyn [48,49]. The Fyn signal is required before the TCR signal, as iNKT cell development is rescued in fyn -/-mice crossed with the iNKT cell TCR transgene [50].…”
Section: Discussionmentioning
confidence: 99%
“…It has been well established that SAP is an essential adaptor due to its capacity to recruit FynT to SLAM and p85 of PI3 K to 2B4, respectively [9,10]. SAP is expressed in activated T, NK and NKT cells, as well as in germinal center B cells [11,12], and is indispensable for normal NKT cell development, generation of a proper Th2 response and Ig class switching in humans and mice [13][14][15][16][17][18]. In XLP patients, both EBV-infected B cells and EBVspecific CTL hyper-proliferate, although the underlying mechanism is still controversial.…”
Section: Introductionmentioning
confidence: 99%